2015
DOI: 10.4103/1735-1995.165951
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cleft lip and palate among four provinces in the West and North-West of Iran

Abstract: Background:One of the most common anomalies in newborn infants is cleft lip and/or cleft palate (CL/P). In spite of several studies about the prevalence of this, no investigation evaluated this prevalence in the West and North-West of Iran. With due attention to different ethnic groups in this area, the aim of this study is to investigate whether the distribution of CL/P live births varies regionally in this area of Iran.Materials and Methods:A cross-sectional study was conducted using hospital registry record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Since possibly the children who were not recognized at birth inside the clinic had not been now collected, therefore we consider all workplace speech and language pathology documents in this place. In the research of Jalilevand et al, the results about CL/P prevalence in four west and north-west provinces of Iran indicated no differences in distribution between boys and girls [9]. Our study similarly suggested that CLP was not significant in girls and boys.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Since possibly the children who were not recognized at birth inside the clinic had not been now collected, therefore we consider all workplace speech and language pathology documents in this place. In the research of Jalilevand et al, the results about CL/P prevalence in four west and north-west provinces of Iran indicated no differences in distribution between boys and girls [9]. Our study similarly suggested that CLP was not significant in girls and boys.…”
Section: Discussionsupporting
confidence: 77%
“…The maximum common type was CLP, and the overall prevalence was 0.93 per 1000 live births. In the study of Namdar et al, this number was 1.2 [8] and it was obtained in west and north-west Iran (0.557, 0.352, 0.503, and 0.559), Tehran City (1.3), and Gorgan City (1.05) [9][10][11]; such variability can be attributed to the geographic place of ethnic origins of the population.…”
Section: We Used Electronic Records (Medical Institutionbased) Of Chi...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, female infants accounted for almost most cases in CP (57.5%) patients. Other investigations reported a larger incidence of CP in females [ 41 – 43 ], as well as a higher incidence of CLP in males [ 12 , 42 , 43 ], with one study finding a male dominance for CL [ 12 ]. Contrary to our study, one paper showed that CL was much higher among females (70%), while another found no significant differences in the incidence of CL between the genders [ 44 ].…”
Section: Discussionmentioning
confidence: 99%